THE EFFECTIVENESS OF THE PICTURE WORD INDUCTIVE MODEL (PWIM) IN TEACHING ENGLISH TO SIXTH-GRADE STUDENTS AT SD NEGERI NO. 4 BALANGNIPA - Nur Hazizah; Ana Mutmainah Bani Said; Nur Fadhilah Syam; Harmilawati; Irmayani (English Education Study Program STKIP PGRI Pacitan, 2025)
This study aims to determine the effectiveness of the Picture Word Inductive Model (PWIM) in improving the English vocabulary mastery of sixth-grade students at SD Negeri No. 4 Balangnipa. The research was motivated by the lack of vocabulary mastery among students due to the use of conventional learning models. A quantitative approach with a quasi-experimental design using a one-group pretest-posttest model was employed. The research sample consisted of 21 students. Data collection techniques included vocabulary tests, observation, questionnaires, and documentation. The data were analyzed using a paired sample t-test. The results showed a significant improvement in vocabulary mastery, as indicated by the increase in students’ average scores from pretest to posttest. Statistical analysis revealed a significance value of 0.000 (p < 0.05), indicating that the PWIM method was effective. Observational data also showed active student participation and positive responses toward the learning model. The PWIM approach, which integrates visual imagery and contextual learning, was proven to enhance students’ engagement and retention of vocabulary. Based on these findings, it can be concluded that PWIM is an effective teaching model for improving English vocabulary mastery in elementary school students.